Developing a Total Preventive Maintenance (TPM) Plan for Flatlock Sewing Machines: A Case Study in the Apparel Industry in Sri Lanka - Silva, S. K. P. N. (Prabandhan: Indian Journal of Management, 2012)
Total Preventive Maintenance (TPM) is a maintenance concept which was originated and developed in Japan. It is useful in reducing machine breakdowns. As a result, companies can improve their productivity and quality and can achieve a competitive advantage over others. TPM was first applied to automotive industry, which then later spread to many other industries in both developed and developing countries. In Sri Lanka, the apparel sector is one of the leaders in implementing TPM concepts. However, a little research work is carried out in regarding its suitability. Therefore, in order to fill this empirical gap, this research is an attempt to develop a maintenance schedule for Flatlock sewing machines, which is used heavily in the apparel sector. The study first undertook literature review in the fields of TPM and Flatlock sewing machines. Then it developed a broader research objective to identify a maintenance schedule in order to minimize breakdowns in Flatlock sewing machines using TPM techniques. The research was administered with one of the leading apparel manufacturers in Sri Lanka using personal interviews, secondary data and observations. The sample production line was selected judgmentally. In analyzing the data, descriptive statistics and qualitative techniques were used. The study developed a maintenance plan to improve the present situation relating to Flatlock sewing machines and tested it empirically. The result of the study revealed that TPM concepts can be effectively used to reduce breakdowns in Flatlock sewing machines. The findings can be extended to other types of sewing machines in similar organizations.